If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = 15q + -50 + -5p Reorder the terms: -15 = -50 + -5p + 15q Solving -15 = -50 + -5p + 15q Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5p' to each side of the equation. -15 + 5p = -50 + -5p + 5p + 15q Combine like terms: -5p + 5p = 0 -15 + 5p = -50 + 0 + 15q -15 + 5p = -50 + 15q Add '15' to each side of the equation. -15 + 15 + 5p = -50 + 15 + 15q Combine like terms: -15 + 15 = 0 0 + 5p = -50 + 15 + 15q 5p = -50 + 15 + 15q Combine like terms: -50 + 15 = -35 5p = -35 + 15q Divide each side by '5'. p = -7 + 3q Simplifying p = -7 + 3q
| (8x-1)(5x+1)=0 | | (5k+3)(k-2)=0 | | -6(3+2k)=-78 | | 5(5r+5)=-100 | | (2x+8)(x-3)=154 | | H=16t(7-t)+10 | | 3t^6*3t^2= | | 6c=11 | | -46=-6x+2 | | Sin^2(x)-sin(x)-1=0 | | 6(x-4)+10=2x-12 | | 115x+25+10x=1400 | | 11=-3-x | | 4v=7 | | 2(m-3)-(2m+6)= | | 9c+8=3 | | x+(x+7)=60 | | N^2-9n+19=0 | | -11=4-8x+1 | | 5n-7=4 | | 48=x^4-5x^2+4 | | 8b+11+2b=2b+2 | | 2(x+2)=16+4x | | 2y=(k+4)x-1 | | 2=8(h-5) | | 0.8+0.4=12 | | 0.8x=0.4 | | 2=3(i-5) | | -9=6a+1-a | | 18.4+8=t | | 3(x-5)=5x-(3-y) | | 3(7x+3)-11(2x+1)=-x-2 |